MAKNA FILOSOFIS PANCA KERTYA DALAM UPACARA POTONG GIGI - gede agus jaya negara (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2023)
Hinduism is a religion based on a belief system. For adherents of Hinduism, especially in Bali, it looks like a religion that is breathed with various religious activities with different procedures for implementation. So that at first glance it seems that Hinduism is a religion that is full of ritual or ceremonial activities, but the reality that can be seen is only a small part of the implementation of religious teachings that have just been carried out by Hindus, especially in Bali, only limited to religious ceremonies with various ceremonial facilities.This Hindu religious ceremony was born from the concept of the Tri Kerangka Dasar of Hinduism namely Tattwa, Susila and upacara, the three of which cannot stand alone and are interrelated with one another. With regard to the basic framework of Hinduism, the most prominent implementation in Bali is the ceremonial system contained in the Panca Yadnya teachings, because the ceremony is the outermost aspect that describes the diversity of the implementation of Hindu religious teachings. In connection with the implementation of the yadnya ceremony, the important material to observe is the value and meaning contained in the procession, in this case it can be related to the five activities in the beryadnya which are called Panca Kertya which consists of five elements, namely: (1) Samhara, namely fusion; (2) Tirobhawa, namely drowning; (3) Utpeti, namely the re-creation ceremony; Sthiti namely maintenance; and Anugraha or pedanan. Potong Gigi ceremony, one of the ceremonies that is often held in Bali, certainly has a Panca Kertya philosophical meaning in its implementationWhen examining the structure of the Potong Gigi ceremony from the Panca Kertya aspect, a conclusion can be drawn that the implementation of the Potong Gigi ceremony has a complete part or procession in an effort to humanize humans to find their identity. Or in other words, between the Potong Gigi ceremony and the teachings of Panca Kertya, it is a religious activity that is unified or integral in building the components of yadnya.